Effective Strategies for Preschool Peer Group Entry: Considered Applications for Children with Visual Impairments. (July 2014) - Ely, Mindy S.
Preschool children with visual impairments (that is, those who are blind or have low vision) have difficulty entering into social play, yet educators lack evidence-based strategies for remediating this social deficit. This literary review identifies strategies from typical children, including entry bids, communication skills, and environmental supports. Application and future research implications are suggested related to children with visual impairments.